Impact of Restless Legs Syndrome on the Sleep Quality in Chronic Obstructive Pulmonary Disease - In, Erdal; Turgut, Teyfik; Ozdemir, Cengiz (Turkish Respiratory Soc, 2016)
Objective: It is well known that various sleep disorders are common in cases of chronic obstructive pulmonary disease (COPD). However, restless legs syndrome (RLS) has not been extensively studied in these patients. The aim of the current study was to investigate the prevalence of RLS and its impact on sleep quality in patients with COPD. Methods: The study included a total of 50 patients with COPD with a mean age of 67.2+/-7.7 years; 39 (78%) were male. The RLS diagnosis was made based on the questionnaire items standardized by the International RLS study group. Dyspnea severity (mMRC), quality of life (CAT), sleep quality [ Pittsburgh sleep quality index (PSQI)], and daytime sleepiness [Epworth sleepiness scale (ESS)] were evaluated using certain specific questionnaires. The subjects were studied in two groups: RLS-positive and RLS-negative groups. Results: In the study population, RLS was detected in 17 (34%) patients. It was found that the RLS-positive subjects had a longer disease duration (p=0.006), a higher hospital admission rate (p=0.008), and lower spirometric values (p=0.023 for FVC; p=0.001 for FEV1). The CAT score was significantly higher in the RLS-positive group (p=0.019). The RLS-positive group had higher PSQI and ESS scores (p<0.001 for both). There were negative correlations between PSQI, ESS scores, and spirometric measures (FVC and FEV1), whereas PSQI and ESS scores had positive correlations with disease duration, mMRC, and CAT scores. Conclusion: In our study, it was observed that RLS is a common condition in patients with COPD. As the duration and severity of COPD increases, RLS becomes more prevalent and sleep quality deteriorates.
Keywords: Chronic obstructive pulmonary disease; restless legs syndrome; sleep quality